The Tradeoff between Travel Time from Home to Hospital and Door to Balloon Time in Determining Mortality among STEMI Patients Undergoing PCI - Di Domenicantonio, Riccardo (PLoS One, 2016)
BACKGROUND: In ST-segment elevation myocardial infarction (STEMI), even in presence of short door to balloon time (DTBT), timely reperfusion with percutaneous coronary intervention (PCI) is hampered by pre-hospital delays. Travel time (TT) constitutes a relevant part of these delays and may contribute to worse outcomes. OBJECTIVE: To evaluate the relationship between TT from home to hospital and DTBT on 30-day mortality after PCI among patients with STEMI. METHODS: We enrolled a cohort of 3,608 STEMI patients with a DTBT within 120 minutes who underwent PCI between years 2009 and 2013 in Lazio Region (Italy). We calculated the minimum travel time from residential address to emergency department where the first medical contact occurred. We defined system delay as the sum of travel time and DTBT time. Logistic regression models, including clinical and demographic characteristics were used to estimate the effect of TT and DTBT on mortality. RESULTS: Among patients with 0–90 minutes of system delay, TT above the median value is positively associated with mortality (OR = 2.46; P = 0.009). Survival benefit associated with DTBT below the median results only among patients with TT below the median (OR for DTBT below the median = 0.39; P = 0.013), (OR for interaction between TT and DTBT = 2.36; p = 0.076). CONCLUSION: TT affects survival after PCI for STEMI, even in the presence of health care systems compliant with current guidelines. Results emphasize the importance of health system initiatives to reduce pre-hospital delay. Utilization of TT can contribute to a better estimate of patient mortality risk in the evaluation of quality of care.